EFEK KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PT. TRANS PANORAMA WISATA - Rumapea, Anggi; Satriawan, Bambang (Universitas Batam, 2019)
Business competition in services is very competitive, especially services of Tour and Travel. Finally, these services businesses competing to attract customers using the services of Tour and Travel respectively. This study aims to identify and analyze the influence of service quality, price, and promotion of the service user satisfaction PT. Trans Travel, the sample size of the sample used in the study was 86 customer respondents. The analytical tool used in this research is simple regression analysis as well as a means of data collection questionnaire respondents. Based on the resulting value of R Square of 0.961 and the value of Adjusted R Square of 0.959 - 95.9% means that customer satisfaction can be explained by the quality of service, price and promotion by 95.9%. While the remaining 4.1% can be explained by other factors. The results of this study indicate that there is significant influence of the variable quality of service to customer satisfaction PT service user. Trans Travel.